39 Bakers: roadmap to profitability through customer management. Issue 4 (15th December 2022) - Jha, Suchita; Gupta, Sunakshi; Kumar, Jitender; Rawat, Sandeep
Abstract : Learning outcomes: 1. To analyze the various business models and choose the best model to contribute maximum profit to the company.2. To understand the importance of customer management with the help of the Net Promoter Score in the food retail context.3. To develop customer loyalty strategies and implement them to improve customer management? Case overview/synopsis: 39 Bakers, a multi-outlet bakery chain in Jammu, India, is run by its founder Gagan. 39 Bakers, through its retail outlets across the Jammu region, offers a variety of products, ranging from bakery items that include blends of Indian and Italian cuisines, offering more than 1000 stock keeping units (SKUs). Through its high-quality offerings at an affordable price range, the brand has carved a niche in the hyper-competitive bakery market of the Jammu region. Gagan, has closely seen the Jammu market and customer preferences and strongly perceived that the customers in the Jammu region are very price sensitive. Thus, he has always been very reluctant to increase the prices of his product offerings at 39 Bakers. He has always believed that any drastic price rise may lead to immediate dissatisfaction and customer churn and therefore has not increased the prices at 39 Bakers for two years in a row. While this decision of Gagan paid off in terms of its popularity and recognition as one of the highly recommended bakery chains among customers, it drastically impacted the bottom line (i.e. profitability) at 39 Bakers, especially in the year 2020–21. Getting popularity at the cost of dipping profitability made Gagan rethink his decision to be protective of price increases at 39 bakers. How can he measure customer satisfaction and loyalty? Which loyalty strategies will work for the huge customer base of Jammu? Should he change his business model from B2C to B2B? How can loyalty be established? How can he manage his existing and loyal customers through price increases? Complexity academic level: The case study is suitable for undergraduate and postgraduate courses in Marketing Management and Retail Marketing. The case study's focus can be on the importance of pricing, business model evaluation, customer management analysis, customer loyalty, Customer Loyalty analysis, and net promoters score. The case can also be useful to entrepreneurs and regulators. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 3: Entrepreneurship.